Human rights and taxation in the digital economy: data tax and the right to science - Jayson S. Lamchek (European Law Open)
Data tax (DT) could re-establish states’ legitimacy by governing economic actors and promoting social solidarity and welfare through benefits. However, the overall impact of DT will depend on decisions about what social benefits DT funds (universal basic income or less expensive public goods) and whether benefits will entrench or challenge harmful business models and practices. Focusing on the right to science (RtS), the paper argues that DT could realise the RtS in the digital age through taxation that exacted not only data rent but also rent on the scientific heritage. Finally, the paper emphasises the need for international coordination to ensure that DT is equitably shared among developed and less developed countries.